The Effects of Weather Shocks on Economic Activity : What are the Channels of Impact? - Acevedo Mejia, Sebastian (IMF Working Papers; Working Paper ;, 2018)
Global temperatures have increased at an unprecedented pace in the past 40 years. This paper finds that increases in temperature have uneven macroeconomic effects, with adverse consequences concentrated in countries with hot climates, such as most low-income countries. In these countries, a rise in temperature lowers per capita output, in both the short and medium term, through a wide array of channels: reduced agricultural output, suppressed productivity of workers exposed to heat, slower investment, and poorer health. In an unmitigated climate change scenario, and under very conservative assumptions, model simulations suggest the projected rise in temperature would imply a loss of around 9 percent of output for a representative low-income country by 2100.